Assessment of periodontal status in pre- and postmenopausal women with chronic periodontitis: A cross-sectional study - Richa Agrawal; Hina Ahmed; Neeharika Soorgani; Laxman Naik; Shyamsunder Reddy; Madhuchander Medabalmi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Periodontitis is inflammation of periodontium. Periodontal disease is associated with various risk factors among which female hormonal alterations such as menopause have been found to be connected with periodontal breakdown and osteoporosis in women. The aim of this study was to determine the periodontal status in pre- and postmenopausal females. Materials and Methods: In this study, 60 female patients were analyzed aged between 40 and 60 years. Group 1 (test) comprised 30 premenopausal women with/without chronic periodontitis and Group II (control) comprised 30 postmenopausal women with/without chronic periodontitis. After recording clinical parameters, the scores were provided using Orthopantomograph for each patient. Paired t-test was applied for intragroup comparison and independent sample t-test was applied for intergroup comparison. The value of P < 0.05 was considered statistically significant. Results: The mean plaque index, gingival index, calculus index, pocket probing depth, and clinical attachment loss scores in the premenopausal group were less as compared to postmenopausal group. Both the groups showed statistically significant differences with T=15.28 and P = 0.01. Conclusion: Postmenopausal women are more susceptible to periodontitis. Hence, precaution and initial management of oral diseases should be the utmost priority in women's health. The effect of sex hormones can be reduced with regular dental examination, maintaining good oral hygiene, and hormonal replacement therapies.